Beyond the Traditional and Non-Traditional Karst Dichotomy: Insights from Sandstone Landforms in the Central Plateau of South America - Santos, Guilherme Lima Brasil dos; Salgado, André Augusto Rodrigues; Travassos, Luiz Eduardo Panisset (Revista Brasileira de Geomorfologia, 2025)
This study analyses two distinct karstic sandstone landscapes—Serra das Galés and Ponte de Pedra (GO)—located in the Central Plateau of South America, Brazil. Considering that the former constitutes a ruiniform relief and the latter a fluviokarst, the objective was to discuss the conceptual boundaries between traditional and non-traditional karst. Based on geomorphological mapping, aerial photogrammetry, and geochemical analyses by X-ray fluorescence (XRF), morphogenetic processes in both areas were investigated. In Serra das Galés, the high silica purity, absence of calcium and magnesium oxides, and the geometry of the features suggest a process dominated by arenization and mechanical collapse (piping). In contrast, at Ponte de Pedra, caves, speleothems, and structural collapses associated with the dissolution of carbonate lenses interbedded within sandstone indicate hybrid morphogenesis. The results challenge the binary classification between traditional karst (in carbonate rocks) and non-traditional karst (in non-carbonate lithologies), suggesting the need to understand karstification as a spectrum of processes that vary according to lithological solubility and erosion mechanisms. This approach is relevant for geomorphological mapping, geoheritage inventories, and the management of areas with geoconservation value developed in mixed or atypical substrates.